Joan of Arcadia. The complete series [videorecording (DVD)] - Tamblyn, Amber; Mantegna, Joe; Steenburgen, Mary; Ritter, Jason, 1980-; Welch, Michael, 1987- (Paramount, 2021)
The award-winning series starring Emmy and Golden Globe®-nominee Amber Tamblyn as Joan Girardi. Just an average teenager going through the typical trials and tribulations of adolescence, Joan and her family moved to Arcadia, where things get complicated as she struggles to find meaning in her ongoing surprise encounters with one important visitor - God.